The relationship between clinical parameters and ultrasonographic enthesitis assessment in patients with spondyloarthritis - Gunay Er; Deniz Palamar; Kenan Akgün; İbrahim Asoğlu and Hidayet Sarı (Archives of Rheumatology, 2024)
Objectives: The study aimed to evaluate the role of ultrasonographic assessment of enthesitis in patients with spondyloarthritis (SpA) in terms of disease activity, functionality, and quality of life. Patients and methods: Ninety SpA patients (57 males, 33 females; mean age: 37.5±9.7 years; range, 18 to 60 years) were included in cross-sectional study between November 2016 and January 2017. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), Bath Ankylosing Spondylitis Functional Index (BASFI), Short Form-12 (SF-12), and Ankylosing Spondylitis Quality of Life (ASQoL) were utilized for clinical evaluation. The clinical evaluation of enthesitis was performed with the Spondyloarthritis Research Consortium of Canada (SPARCC) and Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) via an algometer calibrated to 4 kg/cm2 of pressure. Ultrasound evaluation was performed according to Madrid Sonographic Enthesitis Index (MASEI). A total of 2,610 entheseal sites were examined clinically, and 1,080 were assessed ultrasonographically. Results: A significant proportion of enthesitis (463/1,080) was detected on ultrasonographic evaluation but not with clinical enthesitis score (MASES and SPARCC). Although ultrasonographic entheseal evaluation detected enthesitis in at least one enthesis of all patients, 35 of the patients had no enthesitis with clinical examination. The sites most frequently involved in the entheses were the proximal patellar tendon and Achilles tendon. The MASEI score did not correlate with the MASES, SPARCC, BASDAI, SF-12, and ASQoL but moderately correlated with the C-reactive protein (CRP) level (r=0.348), ASDAS-CRP (r=0.294), and BASFI score (r=0.244). Conclusion: The association of ultrasonography scores with CRP levels and ASDAS-CRP indicates that ultrasonography is effective in detecting inflammation. The MASEI score weakly correlates with functionality but not with quality of life. Ultrasonographic evaluation is invaluable and merits to be incorporated into SpA disease scoring system.